2011
DOI: 10.3928/01477447-20110714-42
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Problems in Total Knee Arthroplasty

Abstract: It is important to avoid underestimating the significance of wound complications following total knee arthroplasty (TKA). Expedient and aggressive care is recommended. Understanding the blood supply to the skin around the knee and measures to prevent wound complications are fundamental to preventing wound problems. A detailed patient history and physical examination will identify high-risk patients and any modifiable risk factors. Operative techniques such as raising full-thickness skin flaps and judicious pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 9 publications
0
42
0
1
Order By: Relevance
“…Alternatively, the preoperative use of soft-tissue expanders may address skin that is severely adherent. 27,28 The techniques of soft-tissue expansion, as well as additional prophylactic and salvage soft-tissue transfers about the knee, are beyond the scope of this article. 26,28…”
Section: Prophylactic Soft-tissue Assessmentmentioning
confidence: 99%
“…Alternatively, the preoperative use of soft-tissue expanders may address skin that is severely adherent. 27,28 The techniques of soft-tissue expansion, as well as additional prophylactic and salvage soft-tissue transfers about the knee, are beyond the scope of this article. 26,28…”
Section: Prophylactic Soft-tissue Assessmentmentioning
confidence: 99%
“…Understanding the blood supply to the skin around the knee is fundamental in order to prevent wound problems. 30 Failure to obtain meticulous closure can result in the development of subcutaneous hematoma. The first step in treating such a wound is to recognise when a problem is present, as well as to know when a minor problem can turn into a major one.…”
Section: Patient Safetymentioning
confidence: 99%
“…In summary, wound management associated with TKR requires expedient and aggressive care. 30 The finer points of the operation. The surgeon must have intimate knowledge of both the instruments and implants they are using, which is helped by experience and the volume of surgeries performed.…”
Section: Patient Safetymentioning
confidence: 99%
“…, 5 - 7 , 11 , 13 - 16 In a literature review, we found variable results. Some series show good results, healing the infection with satisfactory cutaneous coverage of the knee; others show bad results with loss of retail, stiffness and pain in the knee and persistence of infection, which can lead to treatment failure and indication for amputation 11 …”
Section: Introductionmentioning
confidence: 92%
“…Problems with wound healing after total knee arthroplasty reach 20% of cases in some series; 9 , 10 however, wound dehiscence with total exposure of the prosthesis without the possibility of primary closure or secondary healing is very rare, and there are few publications that describe its treatment 5 7 , 11 - 15 …”
Section: Introductionmentioning
confidence: 99%